Upaya Membantu Literasi Anak Berkebutuhan Khusus Disleksia di SDN Jorato Sape - Hanafi, Sri Hardiningsih Hanafi; Mulyadi; Muhammad Rijalul Akbar; Ningsih Komalasari; Fitria Sarnita; Muhammad Ziaulhaq; Anggih Tri Cahyadi (UNIB Press, 2023)
Learning strategies in developing the literacy skills of elementary school children in Bima district can be done through playing while learning. Learning activities carried out by elementary school (SD) teachers in helping students especially in literacy for students with learning difficulties (dyslexia) can be done in various ways. One of them is by implementing game activities in the learning process. The game activities here are the traditional Bima game activities (mpa'a mcimi). This activity can be modified by using word cards (flashcards) in it. Efforts made in helping students with learning difficulties (dyslexia) carried out at Jorato Sape Public Elementary School, Bima Regency used the implementation method which was carried out by checking the initial literacy skills of students in grades 1 to grade 5, implementing play activities, and evaluating. From the initial data, the ability of students' learning difficulties varies, from difficulty distinguishing letters, to difficulty combining syllables. While the application of the team uses games by utilizing word cards (flashcards) in these traditional games. Of the 14 students who had learning difficulties, 4 of them showed changes in recognizing letters better with 2 treatments. While 10 other students have not shown optimal changes. This is due to the lack of time and motivation from within the students.